Peningkatan Kinerja Keuangan Bumdes Melalui Pengelolaan Risiko Likuiditas Dan Risiko Kredit Pada Bumdes Dwi Tunggal Di Desa Tegallinggah - Ni Luh De Erik Trisnawati (ARTHA SATYA DHARMA, 2021)
The purpose of this study was to determine the effect of managing Liquidity risk and Credit risk in BUMDes Dwi Tunggal Tegallinggah Village. This study uses a quantitative approach. Data collection techniques used in this study are the documents of the monthly BUMDes Dwi Tunggal for 36 months taken from period 2017 to 2019. Data analysis technique used in this study is multiple regression with the help of SPSS. The research results in this study stated that Loan to Deposit Ratio (LDR) has a significant egffect on financial performance (ROA). This result is proved by the effect of LDR on ROA on BUMDes Dwi Tunggal Tegallinggah Village has a coefficient value that is positive at 0,720 and the results of testing the hypothesis by t-test found that t-count > t-table (2.248 > 2.035) with a significant value of 0.031 < 0.05. Non Performing Loan (NPL) does not significantly influence the ROA indicated by the coefficient value positive at 0.634 and the results of hypothesis testing using the t-test found that t-count < t-table (1.342 < 2.035) with a significant value of 0.188 > 0,05.